The New Low-Profile WEB 17 System for Treatment of Intracranial Aneurysms: First Clinical Experiences - van Rooij, S.B.T. (AJNR Am J Neuroradiol, 2018)
BACKGROUND AND PURPOSE: The Woven EndoBridge (WEB) is an intrasaccular flow diverter intended to treat wide-neck aneurysms. The latest generation WEBs needed a 0.021-inch microcatheter in the small sizes. Recently, a lower profile range of WEBs compliant with a 0.017-inch microcatheter (WEB 17) has been introduced. We present the first clinical results of treatment of both ruptured and unruptured aneurysms with the WEB 17. MATERIALS AND METHODS: Between December 2016 and September 2017, forty-six aneurysms in 40 patients were treated with the WEB 17. No supporting stents or balloons were used. Twenty-five aneurysms were ruptured (54%). There were 6 men and 34 women (mean age, 62 years; median, 63 years; range, 46–87 years). The mean aneurysm size was 4.9 mm (median, 5 mm; range, 2–7 mm). RESULTS: There were 2 thromboembolic procedural complications without clinical sequelae and no ruptures. The overall permanent procedural complication rate was 0% (0 of 40; 97.5% CI, 0%–10.4%). Imaging follow-up at 3 months was available in 33 patients with 39 aneurysms (97.5% of 40 eligible aneurysms). In 1 aneurysm, the detached WEB was undersized and the remnant was additionally treated with coils after 1 week. This same aneurysm reopened at 3 months and was again treated with a second WEB. One other aneurysm showed persistent WEB filling at 3 months. Complete occlusion was achieved in 28 of 39 aneurysms (72%), and 9 aneurysms (23%) showed a neck remnant. CONCLUSIONS: The WEB 17 is safe and effective for both ruptured and unruptured aneurysms. The WEB 17 is a valuable addition to the existing WEB size range, especially for very small aneurysms.